2020
DOI: 10.1016/j.stem.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection of Pluripotent Stem Cell-Derived Human Lung Alveolar Type 2 Cells Elicits a Rapid Epithelial-Intrinsic Inflammatory Response

Abstract: A hallmark of severe COVID-19 pneumonia is SARS-CoV-2 infection of the facultative progenitors of lung alveoli, the alveolar epithelial type 2 cells (AT2s). However, inability to access these cells from patients, particularly at early stages of disease, limits an understanding of disease inception. Here we present an in vitro human model that simulates the initial apical infection of alveolar epithelium with SARS-CoV-2, using induced pluripotent stem cell-derived AT2s that have been adap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
308
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(341 citation statements)
references
References 59 publications
(77 reference statements)
26
308
3
4
Order By: Relevance
“…Regarding the cell types affected, single cell transcriptome and phenotyping studies show that SARS-CoV-2-induced hyperactivation seems to affect a broad spectrum of cells ranging from epithelial cells of the respiratory tract (16)(17)(18), lining endothelial cells (6,7), cells of the innate immune system, including macrophages and mast cells located in the submucosa of the respiratory tract (15,19), and PBMC (including monocytes, dendritic cells, CD4-and CD8 T-cells) (13,15,20).…”
Section: Cytokine and Chemokine Storm Is A Hallmark Of Acute Respiratmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the cell types affected, single cell transcriptome and phenotyping studies show that SARS-CoV-2-induced hyperactivation seems to affect a broad spectrum of cells ranging from epithelial cells of the respiratory tract (16)(17)(18), lining endothelial cells (6,7), cells of the innate immune system, including macrophages and mast cells located in the submucosa of the respiratory tract (15,19), and PBMC (including monocytes, dendritic cells, CD4-and CD8 T-cells) (13,15,20).…”
Section: Cytokine and Chemokine Storm Is A Hallmark Of Acute Respiratmentioning
confidence: 99%
“…Several recent reports have demonstrated the NF-kB pathway as the central signaling pathway for the SARS-CoV-2 infection-induced proinflammatory cytokine/chemokine response (16)(17)(18)(35)(36)(37). Huang et al showed in a human in vitro model that simulates the initial apical infection of alveolar epithelium with SARS-CoV-2 a rapid transcriptomic change in infected cells, characterized by a shift to an inflammatory phenotype with upregulation of NF-kB signaling and NF-kB target genes by day 1 post-infection, followed by a loss of the mature alveolar program (16). Moreover, SARS-CoV-2 spike protein subunit 1 (CoV2-S1) was shown to induce high levels of NF-kB activations, production of pro-inflammatory cytokines and chemokines (IL-1b, TNFa, IL-6, CCL2), and mild epithelial damage in human bronchial epithelial cells.…”
Section: Cytokine and Chemokine Storm Is A Hallmark Of Acute Respiratmentioning
confidence: 99%
“…To investigate the possibility of viral integration into virus infected cells we analyzed published RNA-Seq data from SARS-CoV-2 -infected cells for evidence of chimeric transcripts, which would be indicative of viral integration into the genome and expression. Examination of these data sets [24][25][26][27][28][29][30] (Fig. S1a-b) revealed a substantial number of host-viral chimeric reads (Fig. 1a-c, S1c).…”
Section: Expression Of Viral-cellular Chimeric Transcripts In Infectementioning
confidence: 99%
“…Cancer Cell 38, November 9, 2020 599 severe disease phenotypes (Huang et al, 2020). Another study supports this hypothesis by showing that increased IL-6 is a shift from alveolar resident macrophages to IL-6-producing monocytederived and recruited macrophages, which are found in bronchoalveolarlavage samples from patients with severe disease (Bost et al, 2020).…”
Section: Commentarymentioning
confidence: 91%
“…The role of IL-6 in cancer biology and anticancer treatments as well as emerging knowledge about the role of IL-6 in COVID-19 has produced a beneficial crosstalk between these two areas of research. For instance, COVID-19 research has benefitted from the adoption of lung cancer in vitro models (Huang et al, 2020), as previously mentioned. Additionally, an understanding of monocyte-and macrophage-mediated IL-6 release as part of the ''cytokine storm'' has played a role in a greater understanding of CAR T therapy response, tumor progression, and COVID-19.…”
Section: Looking To the Future: Covid-19 And Cancermentioning
confidence: 99%